The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2007
DOI: 10.1007/s11596-007-0518-y
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory effects of EPA and DHA on proliferation and apoptosis of pancreatic cancer cells

Abstract: In order to investigate the effects of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA) on the proliferation, apoptosis of pancreatic cancer cell line SW1990 cells and the expression of cyclin E mRNA, the SW1990 cells were treated with different concentrations of EPA or DHA (20, 40, 60 microg/mL) for 0, 12, 24, 36 and 48 h respectively. By using MTT method, the inhibitory effects of EPA or DHA on the cell growth were assayed. Real time PCR was used to detect the expression changes of cyclin E mRNA af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…ω3-PUFAs potently inhibited cell proliferation and induced apoptosis, as indicated by the increased sub-G 1 population, caspase-3 activity and PARP cleavage in human pancreatic cancer cells. These data are in line with studies showing that ω3-PUFAs induce apoptosis [31,32,33,34] in human pancreatic cancer cells.…”
Section: Discussionsupporting
confidence: 91%
“…ω3-PUFAs potently inhibited cell proliferation and induced apoptosis, as indicated by the increased sub-G 1 population, caspase-3 activity and PARP cleavage in human pancreatic cancer cells. These data are in line with studies showing that ω3-PUFAs induce apoptosis [31,32,33,34] in human pancreatic cancer cells.…”
Section: Discussionsupporting
confidence: 91%
“…Suppression of the excessive inflammatory reaction and improvement of the immune function are critical for the early stage of severe trauma healing process. ω-3PUFA, comprised of linoleic acid, eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), is one of the essential fatty acids for human beings, and the two components of ω-3PUFA, EPA and DHA, were found in some studies to provide immune nutrition and inhibit proliferation of cancer cells [3][4][5] . Previous studies showed that ω-3PUFA…”
Section: Discussionmentioning
confidence: 99%
“…DHA has proven capable to reduce the risk of heart disease and inflammatory cytokines (Simopoulos, 2002;Von Schacky, 2007). Additionally, DHA inhibits tumour cells growth (Zhang, Long, Zhang, & Wang, 2007) and it can be consumed as acylglycerol for its moderate absorption and less oxidation compared to the free fatty acid form (Valenzuela, Valenzuela, Sanhueza, & Nieto, 2005). Different methods have been developed to obtain n-3 PUFA extracts (as acylglicerides or free fatty acids) from marine oils; some of those methods have been combined to increase both efficiency and yield of the extraction (Gamez, Noriega, Medina, Ortega, García, & Angulo, 2003).…”
Section: Introductionmentioning
confidence: 99%